STUDI KOMPARASI REGULASI TATA KELOLA SYARIAH BAGI PERBANKAN SYARIAH DI NEGARA-NEGARA MUSLIM MINORITAS - ALI RAMA (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2018)
The sharia governance system (SG) is needed by sharia financial institutions to increase public trust in compliance with sharia principles in the overall operation of their business. The practice of SG sharia financial institutions in various jurisdictions varies according to the legal framework that governs them. Countries with a majority Muslim population may have a legal framework regarding SG that is different from Muslim minority countries. This study aims to conduct a comparative analysis of SG regulation models for Islamic banks in minority Muslim countries, especially in Southeast Asian countries such as Singapore, the Philippines and Thailand. This research also included Indonesia as a representation of the majority Muslim country. Content analysis methods for a number of legal documents are used to achieve the research objectives. This study found that Muslim minority countries were relatively flexible in their arrangement of SG for Islamic banking. For example, in the structure of sharia supervision organizations, Singapore, the Philippines and Thailand adhere to a decentralized system of sharia supervision, ie there is no fatwa authority at the national level. Generally these countries do not regulate in detail about the aspects of SG and allow each financial institution to regulate it themselves and or refer to international institutions.